KEINDAHAN RETORIKA DAN STRUKTUR BAHASA SEBAGAI I'JAZ AL-QUR'AN: ANALISIS SURAH AL-RAHMAN - Abdul Mustolif; Muhammad Ali Mustofa Kamal (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study discusses the miracle of the Qur'an (i'jaz) from the perspective of the beauty of language, especially rhetoric and structure in Surah Al-Rahman. This Surah has a distinctive feature in the form of the repetition of the verse